Prevalence and Predictors of Bacterial Infection in Hospitalized Patients with Liver Cirrhosis - Ranjan, Mukesh Kumar; Neupane, Pradeep; Maharjan, Bigyan; Yadav, Roshan Kumar; Shrestha, Ankit; Shrestha, Hari; Pandey, Neeraj; Tiwari, Aashish (Journal of Gastrointestinal Infections, 2024)
Infections adversely affect the prognosis of patients with liver cirrhosis. The study aimed to analyze the prevalence and the predictors of infections in patients admitted with cirrhosis.After obtaining ethical approval, this retrospective study was conducted at a tertiary care center between April 2021 and January 2024. All the patients admitted with cirrhosis were included. Infections were identified according to the standard definitions.Of the 417 patients (mean age: 54.28 ± 12.61 years; male: 299 [71.70%]), 375 (89.92%) had alcohol-related cirrhosis. The mean Child–Turcotte–Pugh (CTP), Model for End-Stage Liver Disease (MELD), and Model for End-Stage Liver Disease with sodium (MELD-Na) scores were 9.6 ± 2.2, 18.3 ± 8.3, and 20.1 ± 8.3, respectively. Infections were seen in 62 (14.86%) patients. The most prevalent infections were urinary tract infection (26 [6.23%]), spontaneous bacterial peritonitis (18 [4.31%]), bloodstream infection (7 [1.67%]), pneumonia (5 [1.19%]), cellulitis (4 [0.95%]), tuberculosis (3 [0.71%]), and upper respiratory tract infection (2 [0.47%]). Patients with infection had significantly high MELD (p = 0.01) and MELD-Na (p = 0.00) scores, and low albumin (p = 0.04) and sodium (p < 0.001) levels. On univariate analysis, ascites (odds ratio [OR]: 1.85; 95% confidence interval [CI]: 1.07–3.19; p = 0.02), gastrointestinal bleeding (OR: 0.50; 95% CI: 0.26–0.98; p = 0.04), MELD (OR: 1.04; 95% CI: 1.00–1.07; p = 0.01), MELD-Na (OR: 1.05; 95% CI: 1.01–1.08; p < 0.001), albumin (OR: 0.59; 95% CI: 0.36–0.98; p = 0.04), and sodium (OR: 0.93; 95% CI: 0.89–0.98; p < 0.001) predicted the presence of infection. On multivariate analysis, ascites (OR: 2.95; 95% CI: 1.06–8.17; p = 0.03) and the presence of comorbidity (OR: 2.74; 95% CI: 1.02–7.31; p = 0.04) were the only predictors of infection.Infections were present in approximately 15% of the patients with cirrhosis. The presence of ascites and comorbidities predicted infection in admitted cirrhotic patients.
Keywords: infections; liver cirrhosis; peritonitis; predictor; prevalence